The biochemistry and fidelity of synthesis by the apicoplast genome replication DNA polymerase Pfprex from the Malaria parasite Plasmodium falciparum - Kennedy, Scott R. (2011)
Plasmodium falciparum, the major causative agent of human malaria contains three separate genomes. The apicoplast, an intracellular organelle contains a ∼35kb circular DNA genome of unusually high A/T content (>86%) that is replicated by the nuclear encoded replication complex Pfprex. Herein, we have expressed and purified the DNA polymerase domain of Pfprex (KPom1) and measured its fidelity using a LacZ based forward mutation assay. In addition, we analyzed the kinetic parameters for the incorporation of both complementary and non-complementary nucleotides incorporation using Kpom1 lacking the 3′→5′ exonucleolytic activity. KPom1 exhibits a strongly biased mutational spectrum in which the T → C is the most frequent single-base substitution and differs significantly from the closely related E. coli DNA polymerase I (pol I). Using E. coli harboring a temperature sensitive pol I allele, we established that KPom1 can complement the growth defective phenotype at an elevated temperature. We propose that the error bias of KPom1 may be exploited in the complementation assay to identify nucleoside analogs that mimic this base-mispairing and preferentially inhibit apicoplast DNA replication.